2021
DOI: 10.1158/0008-5472.can-20-3747
|View full text |Cite
|
Sign up to set email alerts
|

MYC-Activated LncRNA MNX1-AS1 Promotes the Progression of Colorectal Cancer by Stabilizing YB1

Abstract: Long noncoding RNAs (lncRNA) are involved in tumorigenesis and drug resistance. However, the roles and underlying mechanisms of lncRNAs in colorectal cancer are still unknown. In this work, through transcriptomic profiling analysis of 21 paired tumor and normal samples, we identified a novel colorectal cancer–related lncRNA, MNX1-AS1. MNX1-AS1 expression was significantly upregulated in colorectal cancer and associated with poor prognosis. In vitro and in vivo gain- and loss-of-function experiments showed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…Meanwhile, YBX-1 has the capacity to form an RNA nucleoprotein filament, cooperating with and stabilizing MYC [ 19 , 20 ]. MYC is an attractive target for leukemia therapeutics due to its regulation by multiple signaling cascades, while the co-operator YBX-1 and its regulation of MYC activation is not well understood [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, YBX-1 has the capacity to form an RNA nucleoprotein filament, cooperating with and stabilizing MYC [ 19 , 20 ]. MYC is an attractive target for leukemia therapeutics due to its regulation by multiple signaling cascades, while the co-operator YBX-1 and its regulation of MYC activation is not well understood [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…S3e ). The combination treatment group exhibited the highest levels of necrosis and fibrosis, and even exhibited calcification and foam cells, which indicated a strong therapeutic response 30 (Fig. 3i and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 95%
“…From the 16 core genes identified in this study, we found 3 genes linked with the survival of rectal cancer and 5 genes related to the tumor microenvironment [ 41 ]. Some studies have noted that the MYC/MNX1-AS1/YB1 signaling pathway can drive proliferation and affect survival in colorectal cancer [ 42 ]. We found that TGF- β 1 had a significant impact on multiple genes in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%